Do First Ray-Related Angles Change following Subtalar Arthroereisis in Pediatric Patients? A Radiographic Study - Antonio Mazzotti; Laura Langone; Simone Ottavio Zielli; Elena Artioli; Alberto Arceri; Lorenzo Brognara; Francesco Traina; Cesare Faldini (MDPI AG, 2024)
Introduction: Subtalar Arthroereisis (STA) is a surgical intervention for pediatric flexible flatfoot (PFF), primarily targeting hindfoot alignment by limiting excessive subtalar eversion. However, its effects on forefoot parameters remain underexplored. This study aims to investigate radiological changes following STA in pediatric patients. Materials and Methods: A retrospective analysis was conducted on consecutive patients treated with STA for PFF. First ray-related angles, including the Hallux Valgus Angle (HVA) and the Intermetatarsal Angle (IMA), alongside hindfoot radiological parameters such as the Meary, Calcaneal Pitch, and Costa Bartani angles, were assessed. Subgroup analysis by gender was performed, and correlations between demographic and preoperative radiological parameters were examined. Results: Forty-one patients (81 feet) with an average age of 11.6 years were included, with a mean follow-up duration of 6.4 months. No significant differences were observed in first ray-related angles pre-and postoperatively, with the mean IMA changing from 7.97° to 7.18° and the mean HV angles changing from 9.51° to 8.66°. Noteworthy improvements were seen in flat foot angles, including the Meary, Calcaneal Pitch, and Costa Bartani angles, postoperatively. The age subgroup analysis revealed similar trends in IMA and HVA changes between Group A (who underwent surgery before peak growth) and Group B (who underwent surgery after peak growth). Higher preoperative angles tended to improve, while lower preoperative IMAs and HVAs tended to worsen postoperatively, all remaining within normal ranges. Conclusion: STA showed positive radiological outcomes for PFF treatment, while negligible changes in first ray-related angles were observed. The age subgroup analysis indicated similar trends regardless of operation timing. Higher preoperative angles tended to improve, while lower preoperative angles tended to worsen postoperatively, despite all falling within non-pathological ranges. Further research is warranted to confirm this correlation.